Gerakan Sosial Keagamaan Nahdlatul Ulama Pada Masa Kebangkitan Nasional - Ilim Abdul Halim (UIN Sunan Gunung Djati Bandung, 2017)
Some social analysts regard that religious extention as social phenomena was replaced by technology. It is a instrument to legitimate a lower class or group that no having power by way of alienation process. But religion is one aspect of culture that is infortant in social reality. It could influence social system or it could be influenced the other aspect thruought values, morals or ethics. Nahdlatul Ulama (NU) as phenomena of religious organization, that rised at national awakining period in Indonesia, do religious movement through some social roles or functions. The founding of NU could be realized as a religious movement by way oftheory‟s social movement from Sidney Tarrow and Sartono Kartodirdjo. Result of analysis indicate that the rising of Nahdlatul Ulama is a religious movement, because this oraganization is not only has colletive challenge, common purpose, social solidarity and sustained interaction, but has messinaistic, messinaistic, millenaristic, nativistic, holy war, protec to loval culture, megico-mysticism andappreciate to ancestors.